TANDA DALAM DRAMA “MALAM JAHANAM” KARYA MOTINGGO BOESJE: SEBUAH PENDEKATAN SEMIOTIK - Tri Esthi Pamungkas (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
This paper discusses signs contained in “Malam Jahanam”, a drama written by Motinggo Boesje. Those signs areanalyzed using the semiotic’s approach of Charles Sanders Peirce which is related with icon, index, and symbol.This qualitative research that uses descriptive analytic method aims to describe and explain the meaning andfunction of signs contained in “Malam Jahanam”. Through this analysis, it has been acknowledge that icons andsymbols tend to form characterization, while index tends to form plot, especially foreshadowing plot.